Melittin-encapsulating peptide hydrogels for enhanced delivery of impermeable anticancer peptides. (16th July 2020) - Feng, Jue-Ping; Zhu, Ru; Jiang, Fagang; Xie, Jie; Gao, Chang; Li, Min; Jin, Honglin; Fu, Dehao
Abstract : Anticancer peptides (ACPs) have gained significant attention in the past few years. Abstract : Anticancer peptides (ACPs) have gained significant attention in the past few years. Most ACPs only act toward intracellular targets. However, their low membrane penetrability often limits their anticancer efficacy. Here we developed a novel melittin-RADA28 (MR) hydrogel, composed of RADA28 and melittin, through a peptide fusion method in order to promote the membrane permeability of tumor cells with the membrane-disrupting ability of melittin. As a proof of concept, we loaded the MR hydrogel with a therapeutic peptide, KLA (KLAKLAKKLAKLAK), to show the enhanced delivery efficiency of the hydrogel. Our results demonstrated that the formed melittin-RADA28 -KLA peptide (MRP) hydrogel has a nanofiber structure, sustained release profile, and attenuated hemolysis effects. Compared with free KLA, the MRP hydrogel markedly increased the cellular accumulation of KLA, produced the highest ratio of the depolarized mitochondrial membrane, and decreased cell viability in vitro . Following peritumoral injection, the MRP hydrogel treatment suppressed CT26 tumor growth by more than 85%, compared to controls. In summary, we provide a facile and efficient strategy to enhance the delivery of impermeable peptides to improve their therapeutic efficiency.